2018
DOI: 10.1007/s10552-018-1068-2
|View full text |Cite
|
Sign up to set email alerts
|

Childhood diet and growth in boys in relation to timing of puberty and adult height: the Longitudinal Studies of Child Health and Development

Abstract: Our findings suggest that both childhood diet and growth potential/growth contribute to earlier pubertal timing and taller attained height in males, supporting roles of these factors in PCa development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
1
11
1
Order By: Relevance
“…In our analyses, we modelled timing and tempo of self-reported genital change and found no association with the macronutrient variables. This result is in partial agreement with a German and US study that found higher dietary protein in childhood was consistently predictive of earlier height take-off and peak height velocity (12,46) , but not timing of voice-break (12) . Height take-off and peak height velocity are, respectively, early (G2) and later (G3-4) pubertal events controlled by synergistic changes in growth and gonadal hormone levels (47,48) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our analyses, we modelled timing and tempo of self-reported genital change and found no association with the macronutrient variables. This result is in partial agreement with a German and US study that found higher dietary protein in childhood was consistently predictive of earlier height take-off and peak height velocity (12,46) , but not timing of voice-break (12) . Height take-off and peak height velocity are, respectively, early (G2) and later (G3-4) pubertal events controlled by synergistic changes in growth and gonadal hormone levels (47,48) .…”
Section: Discussionsupporting
confidence: 89%
“…The present study represents one of three cohorts to have assessed macronutrient intake in relation to male puberty (12,13,46) . Historically, boys are under-represented in the literature due to the lack of a menarche-equivalent event that signifies achievement of reproductive competence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that large consumption of sugar and sweet beverages among childhood worldwide exert negative health effects, [ 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ] but the effects on puberty onset are still controversial. Only one prospective study found an association between early sexual development and consumption of sugar-sweetened beverages in a sample of 5583 American girls.…”
Section: Nutrient Intake During Childhood and Timing Of Pubertymentioning
confidence: 99%
“…It is worth considering that girls with energy malnutrition seem to experience menarche at a later age than well-fed girls [ 124 , 125 ].…”
Section: Nutrient Intake During Childhood and Timing Of Pubertymentioning
confidence: 99%
“…A healthy diet is an essential component for meeting proper nutrition requirement for optimal body growth and body weight during childhood [ 1 , 2 , 3 ]. A poor diet can be a result of an imbalanced diet by overeating low-nutrient-dense foods such as refined carbohydrates and sweets and failing to consume other foods with high nutrient density, such as fruits, vegetables, and healthy meats [ 4 ].…”
Section: Introductionmentioning
confidence: 99%